Effectiveness of a Qigong program on sleep quality among community-dwelling older adults with mild to moderate depression: A randomized controlled trial - Phenphop Phansuea; Sookjaroen Tangwongchai; Thanapoom Rattananupong; Vitool Lohsoonthorn; Somrat Lertmaharit (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - The purpose of this study was to determine the effectiveness of a Qigong program on older adults in the Thai community suffering from mild to moderate depression. Design/methodology/approach - A randomized controlled trial study was conducted in a public health service (PHS) center setting. Sixty-six older adults aged 60-90 years with mild to moderate depressive symptoms measured by the Thai Geriatric Depression Scale (TGDS: scores 13-24) were recruited and randomly allocated into two groups. The subjective sleep quality was assessed using the Thai version of the Pittsburgh Sleep Quality Index (TPSQI). The Qigong program group was given 12 weeks of Qigong training including three sessions per week, while the control group followed normal PHS activities (singing and praying). The outcome measure was the change in the TGDS from baseline to 12 weeks. Findings - Participants in the Qigong program group had a significantly improved TPSQI global score (p < 0.001), subjective sleep quality (p < 0.001), and sleep latency (p < 0.05) after 12 weeks of intervention, while those in the control group showed no significant difference in sleep quality. Compared with the control group, the Qigong program group reported significantly better sleep quality throughout the 12-week period. The prevalence of poor sleep quality in this population was 82 percent. Originality/value - This study confirmed that the Qigong program could improve sleep quality in older adults with mild to moderate depressive symptoms as the Qigong program conferred more significant improvements than the usual program.